Translating Code-Switching on the Screen: Spanglish and L3-as Theme - Corrius, Montse; Zabalbeascoa, Patrick (Journal of Audiovisual Translation, 2019)
This paper outlines the complexity of accounting for multilingual audiovisual films for the purpose of their translation. In particular it focuses on an issue that has not received much scholarly attention so far, the fictional representation of code-switching in feature films, with particular attention to Spanglish, given that language and its interlinguistic barriers towards interpersonal communication is one of the main themes of the film. The paper distinguishes different types of language shifts (alternations) as part of a film’s plot or script, like straightforward translation between characters, in order to better characterize code-switching as concept borrowed from sociolinguistics. This, in turns allows for a broader notion of language shifts, of which code-shifting is a part. Finally, the paper also includes a three-type classification of films depending on the amount and importance of languages other than the main language of a film: anecdotal, recurrent, and L3-as-theme, L3 being the notation system used to label all instances of languages in a text (written, oral or audiovisual) other than the main language.